IMPLEMENTASI MODEL (PBL) BERBANTUAN APLIKASI BUDAYA INDONESIA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PANCASILA PESERTA DIDIK KELAS IV SD NEGERI SUMOBITO 1 - Saifuddhin, Hadi; Suprayitno, Suprayitno; Zuliana, Deni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The type of Classroom Action Research (PTK) used in this experiment. The focus is on improving Pancasila activities and learning outcomes by implementing the Problem-Based Learning model, assisted by Indonesian culture application media for class IV students at Sumobito I State Elementary School. As a result, aspects of activities and teaching and learning outcomes in each cycle show a significant increase. Where the first cycle of teacher activities obtained a percentage of 75% and the second cycle obtained a percentage of 90%. Likewise with student activities, in cycle I the percentage gain was 76.45% and cycle II 84.55% which shows an increase. For complete learning outcomes in cycle I, the percentage was 70.5% and the increase in cycle II was 88.23%. Based on these data, it was concluded that applying the Problem-Based Learning model assisted by Indonesian cultural application media for class IV students at SDN Sumobito I was able to improve the learning process for Pancasila subjects, especially aspects of teacher activities and student learning outcomes.